Occurrence of paradonition diseasts in inhabitants of Cracov (XI-XVIII centuries) - Gleń, Elżbieta (Anthropological Review, 1976)
An analysis of cranial dentition results from the Cracov District from XI-th to the XVIII centuries is reported. The observations concerned paradontium diseases. It is found that a lowering of the prosessus alveolaris occurs more frequently where usure caries as well as tartar deposits in seniles are present. Diseases of this kind more frequently affected the processus alveolaris of the jawbone. No increase in paradontium diseases due to development of civilisation or differences with regard to sex, were found.